Morphology and SSR Markers-Based Genetic Diversity Analysis of Sesame (Sesamum indicum L.) Cultivars Released in China - Zhen Wang; Fang Zhou; Xuehui Tang; Yuanxiao Yang; Ting Zhou; Hongyan Liu (Agriculture, 2023)
Sesame is a highly valuable crop with significant global importance due to its nutritional and economic value. To better understand the genetic diversity of sesame genotypes at both molecular and morphological levels, a comprehensive study was conducted using 25 pairs of simple sequence repeat (SSR) primers and 56 biological traits in a collection of 183 sesame accessions, which comprised 101 Chinese cultivars, 62 landraces, and 20 exotic accessions. The analysis revealed a total of 166 SSR polymorphic bands, with an average of 6.64 bands per marker. The values of Shannon’s information index ranged from 0.2732 to 0.6497, indicating a moderate level of genetic diversity. The polymorphic information index ranged from 0.0859 to 0.6357, further supporting the presence of genetic variation. The average frequency of heterozygous genotypes was calculated as 0.34, suggesting a relatively narrow genetic diversity. The application of the unweighted pair group method with arithmetic averaging (UPGMA) clustering and principal component analysis allowed for the categorization of the 183 sesame accessions into three distinct groups. Furthermore, the genetic diversity coefficient of sesame germplasm is generally constrained, with no significant difference observed between the genetic diversity coefficient of Chinese cultivars and that of foreign resources. The results provide valuable data for various applications, including the breeding and promotion of new sesame cultivars in China, the protection of new variety rights, the inquiry and identification of DNA genetic information of cultivars, as well as the development and utilization of sesame germplasm resources both domestically and internationally.